Analisis pengaruh kredit perbankan terhadap pertumbuhan ekonomi Kota Jambi - Maherika Maherika; Rahma Nurjanah; Erni Achmad (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to: 1) To find out and analyze the development of working capital loans, investment loans, consumer loans and the Economic Growth of the City of Jambi in the period 2002 - 2017; 2) To find out and analyze the effect of working capital loans on the economic growth of the City of Jambi in the period 2002 - 2017; 3) To find out and analyze the effect of investment credit on the economic growth of Jambi City in the period 2002 - 2017; and 4) To find out and analyze the effect of consumer credit on the economic growth of Jambi City in the period 2002 - 2017. The research analysis tool uses simple regression analysis tools. Based on the results of multiple linear regressions that working capital loans and investment loans have a significant effect on the economic growth of the City of Jambi, while consumer loans do not have a significant effect on the economic growth of the City of Jambi. Keywords: Working capital loans, Investment loans, Consumptive loans, Economic Growth